Matriks Metallopeptidaz 1 geni rs1799750 polimorfizmi ile açık kapanış vakaları arasındaki ilişkinin incelenmesi - Yılmaz, Özlem Özge (My University, 2024)
Amaç: Bu çalışma, bağ dokularının yıkımını düzenleyen kollajenaz enzimini kodlayan MMP-1 genindeki rs1799750 polimorfizminin açık kapanış maloklüzyonunun gelişimi üzerindeki potansiyel etkisini araştırmayı amaçlamaktadır. Gereç ve Yöntem: Çalışmamızda, yaşları 15 ile 35 yaş arası olan açık kapanış tanısı almış 30 hasta ve 30 sağlıklı olmak üzere toplam 60 birey yer almıştır. Yanak içi oral epitel hücreleri bukkal sürüntü yöntemiyle toplanmıştır ve DNA izolasyonu için PureLink kiti kullanılmıştır. MMP-1 rs1799750 polimorfizminin genotiplemesi için gerçek zamanlı PZR (Real-Time PCR) yöntemi kullanılmıştır. Elde edilen sonuçlar istatistiksel olarak değerlendirilmiş ve anlamlılık düzeyi p<0,05 olarak kabul edilmiştir. Bulgular: Çalışmamızda, hasta ve sağlıklı gruplarında MMP-1 genindeki rs1799750 polimorfizminin genotip dağılımı benzer bulunmuştur (sırasıyla %43,3, %23,3, %33,3 ve %36,7, %43,3, %20,0). Gruplar arasında MMP-1 genotip dağılımı ve allel dağılım açısından da anlamlı fark bulunmamıştır (sırasıyla p=0,2269 ve p=0,7125). Ancak, hasta grubu içinde MMP-1 rs1799750 gen polimorfizmi genotip dağılımı ve allel dağılımı açısından karşılaştırıldığında, istatistiksel olarak anlamlı farklılık bulunmuştur (sırasıyla p=0,009 ve p<0,001). 0 ve -0,9 mm açık kapanışa sahip bireylerde 1G/ 1G genotipi ve 1G alleli daha yaygın bulunmuştur (%76,9 ve %66,7); -1 mm ve üzeri açık kapanışa sahip bireylerde ise 2G alleli daha yaygın nulunmuştur (%51,9). Sonuç: Açık kapanış maloklüzyonu olan bireylerde overbite şiddeti arttıkça 2G alleli artar. MMP-1 rs1799750 polimorfizmi, yüksek MMP-1 üretimi ile ilişkilendirilir ve bu, ekstraselüler matriks yıkımına yol açar. Bu nedenle, MMP-1 rs1799750 polimorfizmindeki 2G alleli, açık kapanış maloklüzyonu riskini artırabilir.

Objective: This study aims to investigate the potential effect of rs1799750 polymorphism in the MMP-1 gene, which encodes the collagenase enzyme that regulates the destruction of connective tissues, on the development of open bite malocclusion. Materials and Methods: A total of 60 individuals, 30 patients diagnosed with open bite and 30 healthy individual as controls, aged between 15 and 35 years, were included in our study. Buccal oral epithelial cells were collected by buccal swab method and PureLink kit was used for DNA isolation. Real-Time PCR method was used for genotyping the MMP-1 rs1799750 polymorphism. The results obtained were evaluated statistically and the significance level was accepted as p<0.05. Results: In our study, the genotype distribution of MMP-1 rs179970 polymorphism was found to be similar in the patient and healthy groups (43.3%, 23.3%, 33.3% and 36.7%, 43.3%, 20.0%, respectively). There was no significant difference between the groups in terms of MMP-1 genotype distribution and allelic distribution (p=0.2269 and p=0.7125, respectively). However, when MMP-1 rs1799750 gene polymorphism was compared in terms of genotype distribution and allelic distribution in the patient group, a statistically significant difference was found (p=0.009 and p<0.001, respectively). The 1G/ 1G genotype and the 1G allele were found to be more common in individuals with 0 and -0.9 mm open bite (76.9% and 66.7%); The 2G allele was found to be more common in individuals with an open bite of -1 mm or more (51.9%). Conclusion: In individuals with open bite malocclusion, the 2G allele increases as the severity of overbite increases. The MMP-1 rs1799750 polymorphism is associated with increased MMP-1 production, leading to extracellular matrix degradation. Therefore, the 2G allele in the MMP-1 rs1799750 polymorphism may increase the risk of open bite malocclusion.
Investigation of the relationship between Matrix Metallopeptidase 1 gene rs1799750 polymorphism and open bite cases
Keywords: Açık kapanış; genetik; Malocclusion; Maloklüzyon; MMP-1; open bite; Orthodontics, Corrective; Ortodonti, Düzeltici; polimorfizm Genetics; polymorphism